Community treatment orders and social factors: complex journeys in the mental health system. Issue 4 (2nd October 2019) - Haynes, Philip; Stroud, Julia
ABSTRACT: Community Treatment Orders (CTOs) have developed rapidly in England and Wales to become a substantial legal intervention. Mixed methods were used to analyse CTOs as one intervention in a complex mental health system and its relationship with social factors. CTOs are used more than expected, with a high number of revocations and renewals. Less than half of CTOs are discharged on time. Service users experience multiple social disadvantages and isolation. They value the stability of a relationship with a care coordinator, but are ambivalent about medication, and can have negative feelings about coercion. Those experiencing recovery tend to initiate social activities, but have poor engagement in care plans, tribunals and reviews. CTOs reduce compulsory hospitalisation, but give rise to human rights issues in the community. Without major social investment to support those with chronic mental health conditions, CTOs may remain the best compromise to balance the demands and requirements of legal and health policy.